1997
DOI: 10.1161/01.str.28.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asymptomatic Retinal Emboli in an Australian Urban Community

Abstract: This study provides accurate prevalence rates for asymptomatic retinal emboli in the elderly and confirms associations with hypertension, smoking, and vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 23 publications
5
46
1
Order By: Relevance
“…8,12 We found no significant gender difference in embolus incidence, contrasting with previous reports. 8,9,12 Our data confirm previous reported associations between retinal emboli and traditional cardiovascular risk factors, including hypertension, 8 -11 smoking, 8 -12 hypercholesterolemia, 3,8 -12 and plasma fibrinogen. 8,9,11,12 In hypertensive subjects who smoked, a 4.4-fold risk of emboli over nonsmokers …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…8,12 We found no significant gender difference in embolus incidence, contrasting with previous reports. 8,9,12 Our data confirm previous reported associations between retinal emboli and traditional cardiovascular risk factors, including hypertension, 8 -11 smoking, 8 -12 hypercholesterolemia, 3,8 -12 and plasma fibrinogen. 8,9,11,12 In hypertensive subjects who smoked, a 4.4-fold risk of emboli over nonsmokers …”
Section: Discussionsupporting
confidence: 89%
“…13 Photographs were assessed for embolus type (cholesterol, fibrin-platelet, calcific), number, location and size, 9 and retinal vascular signs (focal arteriolar narrowing, arteriovenous [AV] nicking, opacification of the arteriolar wall), and presence of retinopathy lesions. 14 At baseline, we measured blood pressure (BP) and defined mean arterial BP (MABP) as one third systolic BP (SBP)ϩtwo thirds diastolic BP (DBP), severe hypertension if SBP Ն160 mm Hg/DBP Ն100 mm Hg or use of antihypertensive medications, and overweight if body mass index Ն25.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 5.2% of cardiac patients had asymptomatic retinal emboli before coronary catheterization, which is substantially higher than the reported prevalence of 1.4% found in a general older Australian population 9 (Table). This finding suggests that patients undergoing cardiac catheterization may also have an increased risk of stroke, as retinal emboli are known to predict higher stroke risk.…”
Section: Discussioncontrasting
confidence: 60%
“…1,2 Retinal emboli, particularly cholesterol emboli (Hollenhorst plaques), are frequently observed in asymptomatic patients and are associated with an increased risk for stroke and vascular death, but not with ICA lesions. [3][4][5][6] Transcranial Doppler ultrasonography (TCD) studies have demonstrated microembolic signals (MES) in the basal vessels of the brain in patients with cerebral and retinal ischemia, cardioembolic lesions, and ICA stenosis. [7][8][9][10] MES are common in patients with retinal ischemia and are associated with ICA stenosis in these patients.…”
mentioning
confidence: 99%